2015
DOI: 10.1002/jbm.b.33402
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of silk fibroin film using centrifugal casting technique for corneal tissue engineering

Abstract: Films prepared from silk fibroin have shown potential as biomaterials in tissue engineering applications for the eye. Here, we present a novel process for fabrication of silk fibroin films for corneal application. In this work, fabrication of silk fibroin films was simply achieved by centrifugal force. In contrast to the conventional dry casting method, we carried out the new process in a centrifuge with a rotating speed of 4000 rpm, where centrifugal force was imposed on an aluminum tube containing silk fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 38 publications
(45 reference statements)
0
24
0
1
Order By: Relevance
“…Many of the previously published regeneration processes result in the dissolution of these structures, which in particular have been recently recognized as the key to the high performance of native silk [46,47]. However, the dissolution of silk in FA/CaCl 2 solution may also be regarded as advantageous, because the resulting fibers exhibit fibrillary structures of high hierarchical order, higher strength and increased extensibility, especially when compared to conventional manufacturing methods of native silk [48].…”
Section: Discussionmentioning
confidence: 99%
“…Many of the previously published regeneration processes result in the dissolution of these structures, which in particular have been recently recognized as the key to the high performance of native silk [46,47]. However, the dissolution of silk in FA/CaCl 2 solution may also be regarded as advantageous, because the resulting fibers exhibit fibrillary structures of high hierarchical order, higher strength and increased extensibility, especially when compared to conventional manufacturing methods of native silk [48].…”
Section: Discussionmentioning
confidence: 99%
“…Upon centrifugation, the fabricated disk‐shaped tissue had a uniform thickness, while the tissue fabricated without centrifugation had a markedly nonuniform thickness. In another example, silk fibroin films used in corneal tissue engineering were fabricated by centrifugal casting and found that the films had less surface roughness than those fabricated without a centrifuge . These studies imply that adjusting the inclination angle against the horizontal plane would be important to fabricate flat and smooth tissues or biomaterials, particularly when large centrifugal force was used.…”
Section: Discussionmentioning
confidence: 99%
“…First, we could make the reverse‐image casting moulds using a DLP 3D printer, and it allows the centrifugal force to be applied to the biomaterials, resulting in greater homogeneity of the final internal fixation systems. Previously, we demonstrated that the centrifugal casting technique can be used to produce a more homogeneous SF film than a dry casting approach (Lee et al, ). In this study, we also observed on the scanning electron microscope (SEM) images that our fabricated SF screws have a smooth surface profile and quite compact inner architecture.…”
Section: Discussionmentioning
confidence: 99%
“…The casting moulds were placed into the centrifugal head on a centrifuge and were subsequently filled with 30% w/v SF solution. To achieve uniform distribution and solidification of the SF solution, each centrifuge machine was rotated at a speed of 3,000 rpm for 4 hr (Lee et al, ). Next, the SF‐permeated casting moulds were placed in an oven at 60°C for 10 min to remove moisture within the casting moulds.…”
Section: Methodsmentioning
confidence: 99%